2013
DOI: 10.1371/journal.pcbi.1003191
|View full text |Cite
|
Sign up to set email alerts
|

Visual Nonclassical Receptive Field Effects Emerge from Sparse Coding in a Dynamical System

Abstract: Extensive electrophysiology studies have shown that many V1 simple cells have nonlinear response properties to stimuli within their classical receptive field (CRF) and receive contextual influence from stimuli outside the CRF modulating the cell's response. Models seeking to explain these non-classical receptive field (nCRF) effects in terms of circuit mechanisms, input-output descriptions, or individual visual tasks provide limited insight into the functional significance of these response properties, because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
109
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 74 publications
6
109
0
Order By: Relevance
“…The sparse coding model has been shown to account for many observed response properties in the primary visual cortex (V1), including classic receptive field structure 3,4 and nonclassical response modulations. 5 Furthermore, recent electrophysiology studies also appear to support this coding model. [6][7][8] While there is some debate about the role of sparse coding in biophysical systems, 9,10 some of these criticisms themselves have led to rebuttals in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…The sparse coding model has been shown to account for many observed response properties in the primary visual cortex (V1), including classic receptive field structure 3,4 and nonclassical response modulations. 5 Furthermore, recent electrophysiology studies also appear to support this coding model. [6][7][8] While there is some debate about the role of sparse coding in biophysical systems, 9,10 some of these criticisms themselves have led to rebuttals in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, some other studies have reported that several classical receptive field (CRF) and non-classical receptive field (nCRF) response properties of single neurons are well simulated by sparse representation [22]- [24]. To further testify this hypothesis, we use a neurally plausible sparse representation model to simulate the emergence of several known simple cell response properties.…”
Section: Introductionmentioning
confidence: 93%
“…However, most of the effects observed in experiments are caused by stimuli extending far beyond the 75 range of the recorded neuron's input fields Polat et al (1998);Walker et al (2000); Mizobe et al (2001). 76 Hence the mechanism put forward by this model Zhu and Rozell (2013) can only be a valid explanation for 77 a small part of these effects, covering situations in which the surround is small and in close proximity to 78 the cRF. This observation raises the important question, how sparse coding models have to be extended 79 to better reflect cortical dynamics and anatomical structure.…”
mentioning
confidence: 99%
“…Recently, Zhu and Rozell reproduced a variety of key effects such as surround suppression, cross-67 orientation facilitation, and stimulus contrast-dependent ncRF modulations Zhu and Rozell (2013). In 68 their framework, small localized stimuli are best explained by activating the unit with the optimal match 69 between its input field ('dictionary' vector).…”
mentioning
confidence: 99%
See 1 more Smart Citation